Impressions from the International Days of Study (Fiep Bulletin - online, 2015)
The Decision to invite representatives of scientists working within the field of physiology, medical men and teachers with practical experience within the same field to a five day conference to discuss the problem “physical education for girls during the age of puberrty” must be given the greatest recognition. First and  foremost we must thank the organization.
Keywords: .